Influence of Capital, Working Hours, Storage Technology and Business Location On the Income of Fish Traders in the Regional Market of West Denpasar District - Sasmita, Wirdatama; Yuliarmi, Ni Nyoman (Business and Investment Review, 2025)
This study aims to analyze the influence of capital, working hours, storage technology, and business location on the income of fish vendors in the Regional Markets of West Denpasar District. The background of the study is based on the essential role of fish vendors as the primary link between fishermen and the community in meeting the fish consumption needs in West Denpasar. As one of the areas with major traditional markets, West Denpasar District holds great potential in the fish trading sector. However, fish vendors in the regional markets of West Denpasar still face various challenges in increasing their business income. This research uses a quantitative approach with an associative design. The sample was determined proportionally using proportionate stratified random sampling, while respondents were selected through accidental sampling at the five regional markets in West Denpasar District. Primary data were collected through observation, interviews, and questionnaires, while secondary data were obtained from relevant government agencies and market officials. Data were analyzed using multiple linear regression, supported by classical assumption tests, F-test, and t-test to examine the significance of the independent variables both simultaneously and partially, The results indicate that capital, working hours, storage technology, and business location simultaneously have a significant effect on the income of fish vendors in the Regional Markets of West Denpasar District. Partially, capital, storage technology, and business location have a positive and significant effect on income. However, the working hours variable shows a positive but not significant effect